The effect of additional dadih on lactic acid bacteria and nutritional value of pudding as a food supplementation - Helmizar,; Azrimaidaliza,; Restu Sakinah,; Arief Yandri, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Dadih is a dairy product obtained from fermented buffalo milk in West Sumatra, Indonesia. It contains various nutrients and probiotics that are beneficial for prenatal supplementation and pregnancy outcomes. In this study, a pudding enriched with dadih was formulated. The study was conducted in November-December 2019 at the Nutrition Laboratory Andalas University. The design of this study was a True Experiment using a Completely Randomized Design (CRD) with two replications consisting of four formulas. They were F0, F1, F2, and F3 with the addition of dadih at 0, 80, 90, and 100 g, respectively. Analysis of nutritional value and the number of Lactic Acid Bacteria (LAB) was performed. Based on the nutritional value analysis, 100 g of dadih pudding contains 11.59% of carbohydrate, 1.24% of protein, 1.09% of fat, with a total of 61.13 calories for F0; 10.41% of carbohydrate, 2.29% of protein, 3.29% of fat, with a total of 80.41 calories for F1; 10.12% of carbohydrate, 4.74% of protein, 3.32% of fat, with a total 89.32 calories for F2; and 11.84 % of carbohydrate, 3.05% of protein, 3.13% of fat, with a total 87,73 calories for F3. The result of the LAB test of dadih pudding showed that: F0 at 3.1 × 103 (CFU/g); F1 at 1.7 × 109 (CFU/g); F2 at 2.4 × 109 (CFU/g), and F3 at 2.4 × 109 (CFU/g). While the result of the Kruskall Wallis test showed that there was a significant difference between the hedonic test and the hedonic quality test of four dadih pudding formulas (p<0.000). The chosen formula was F3 with the highest nutrition value average of 87.73 kcaL total calories. Dadih pudding is recommended as a food supplementation because it is good for the digestive system and can increase the immune system of pregnant women.